2020
DOI: 10.1038/s41423-020-00560-0
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils in liver diseases: pathogenesis and therapeutic targets

Abstract: Previously, it was assumed that peripheral neutrophils are a homogeneous population that displays antimicrobial functions. However, recent data have revealed that neutrophils are heterogeneous and are additionally involved in tissue damage and immune regulation. The phenotypic and functional plasticity of neutrophils has been identified in patients with cancer, inflammatory disorders, infections, and other diseases. Currently, neutrophils, with their autocrine, paracrine, and immune modulation functions, have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
122
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(129 citation statements)
references
References 88 publications
5
122
0
2
Order By: Relevance
“…The existence of cell subpopulations in distinct differentiation states fully reflects the complexity and diversity of GBC in its evolution. In previous studies, neutrophil-to-lymphocyte ratio (NLR) showed prognostic significance in GBC patients (32) and increasing neutrophil levels have a significant influence on the TME by inducing various cytokines and chemokines, which could accelerate the proliferation and promote metastasis of tumor cells (33,34). Thus, targeting neutrophils might become a new direction for the treatment of GBC metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…The existence of cell subpopulations in distinct differentiation states fully reflects the complexity and diversity of GBC in its evolution. In previous studies, neutrophil-to-lymphocyte ratio (NLR) showed prognostic significance in GBC patients (32) and increasing neutrophil levels have a significant influence on the TME by inducing various cytokines and chemokines, which could accelerate the proliferation and promote metastasis of tumor cells (33,34). Thus, targeting neutrophils might become a new direction for the treatment of GBC metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…The existence of cell subpopulations in different differentiation states fully re ects the complexity and diversity of GBC in its evolution. In previous studies, neutrophil-to-lymphocyte ratio (NLR) showed prognostic signi cance in GBC patients [35] and increasing neutrophil levels have a signi cant in uence on the TME by inducing various cytokines and chemokines which could accelerate the proliferation and promote metastasis of tumor cells [36,37]. Targeting neutrophils might become a new direction for the treatment of GBC metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, macrophages contribute to liver fibrogenesis by secreting TGFβ, which is the most potent fibrogenic cytokine for HSC activation [5]. Neutrophils likely promote liver fibrosis via production of ROS but may also promote liver fibrosis resolution by transferring microRNA into macrophages [6][7][8][9]. Moreover, natural killer cells have been reported to kill activated HSCs, thereby inhibiting liver fibrosis [10].…”
Section: Ivyspringmentioning
confidence: 99%